2011
DOI: 10.1007/s00535-011-0414-x
|View full text |Cite
|
Sign up to set email alerts
|

Serodiagnosis of Helicobacter hepaticus infection in patients with liver and gastrointestinal diseases: western blot analysis and ELISA using a highly specific monoclonal antibody for H. hepaticus antigen

Abstract: H. hepaticus infection might play a role in the development of liver diseases; in particular, it might increase the risk of the development of HBV- and/or HCV-infected liver diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 17 publications
1
12
0
1
Order By: Relevance
“…H. hepaticus infection has been suggested to accelerate the progression of HBV and HCV infection. (31) The present study showed that the rate of positive detection of anti-H. …”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…H. hepaticus infection has been suggested to accelerate the progression of HBV and HCV infection. (31) The present study showed that the rate of positive detection of anti-H. …”
Section: Discussionsupporting
confidence: 50%
“…(31) The highest H. hepaticus antigen level was found in the sera of patients with hepatic cirrhosis, followed by that in the sera of patients with hepatitis complicated by HBV or HCV infection. These groups had H. hepaticus antigen levels that were significantly higher than those in patients with common liver diseases.…”
Section: Discussionmentioning
confidence: 95%
“…Subsequent procedures were performed using an ELISA kit according to the manufacturer's instructions. 22 After 20 minutes at room temperature, a slat was taken from the sealed foil for creation of sample and standard holes. Sample holes were added to test 10 µL samples first, after which the diluent sample volume added was 40 µL.…”
Section: Pathologic Observations On Elisamentioning
confidence: 99%
“…A meta-analysis based on a systematic review of 18 studies published between 1998 and 2011 revealed a significantly higher pooled infection rate for H. pylori and Helicobacter hepaticus in patients with lithiasis [5]. In another study from Japan, Murakami et al [6] found increased concentrations of anti-H. hepaticus antibodies in the sera of patients with liver disease compared with those suffering from other groups using ELISA and western blot with the new monoclonal antibody HR II-51. The authors concluded that H. hepaticus infection might play a role in the development of liver disease, especially in HBV and/or HCV-infected patients.…”
Section: Hepatobiliary Diseasementioning
confidence: 99%